2008
DOI: 10.1189/jlb.0608347
|View full text |Cite
|
Sign up to set email alerts
|

TWEAK is expressed at the cell surface of monocytes during multiple sclerosis

Abstract: The TNF superfamily ligand, TNF-like weak inducer of apoptosis (TWEAK), regulates cellular responses ranging from proliferation to cell death in a manner highly dependent on the cell type and the microenvironmental context. We have shown previously that treatment of experimental autoimmune encephalomyelitis mice after the priming phase with neutralizing anti-TWEAK antibodies results in a reduction in the severity of the disease and leukocyte infiltration. To further characterize TWEAK/fibroblast growth factor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 22 publications
1
28
1
Order By: Relevance
“…Recently, research has revealed that TWEAK could be observed in lymphocytes and/or monocytes in patients with multiple sclerosis [47], and cell-surface expression of TWEAK has also been reported on human monocytes after IFN exposure in culture [48] and on T cells from patients with systemic lupus erythematosus [32,49]. Intracellular TWEAK could be observed in lymphocytes (T cells and B cells) and monocytes from SLE patients [50]. Fn14 receptor is the cognate receptor for TWEAK.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recently, research has revealed that TWEAK could be observed in lymphocytes and/or monocytes in patients with multiple sclerosis [47], and cell-surface expression of TWEAK has also been reported on human monocytes after IFN exposure in culture [48] and on T cells from patients with systemic lupus erythematosus [32,49]. Intracellular TWEAK could be observed in lymphocytes (T cells and B cells) and monocytes from SLE patients [50]. Fn14 receptor is the cognate receptor for TWEAK.…”
Section: Introductionmentioning
confidence: 96%
“…TWEAK mRNA is ubiquitously expressed, and the expression is increased after injury including in LN [5,9,21,33,36,[39][40][41][42]. It is thought to be expressed primarily as a soluble cytokine as a result of efficient furin-mediated cleavage along the secretory pathway [43], largely produced as a soluble cytokine by immune cell types [44,45], such as monocytes/macrophages, dendritic cells, and natural killer cells [46,47]. Recently, research has revealed that TWEAK could be observed in lymphocytes and/or monocytes in patients with multiple sclerosis [47], and cell-surface expression of TWEAK has also been reported on human monocytes after IFN exposure in culture [48] and on T cells from patients with systemic lupus erythematosus [32,49].…”
Section: Introductionmentioning
confidence: 99%
“…Since monocytes/macrophages have been shown to express TWEAK [11] we hypothesized that increased production of TWEAK by the peripheral blood mononuclear cells (PBMC) might be a source of increased levels of TWEAK in the blood of SSc patients. To address this hypothesis, the production of TWEAK was investigated in the PBMC from patients with SSc and healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, activated renal macrophages are markers of disease onset in lupus nephritis [15]. We hypothesized that macrophages, as a result of both FcR engagement by immune complexes deposited in the glomeruli [16], Fn14 engagement by TWEAK, and/or active secretion of TWEAK [4][5][6], would play a critical role in initiating and amplifying the inflammatory cascade that culminates in lupus nephritis, and that their depletion would reveal this unique role by effectively reducing kidney damage.…”
Section: Non-essential Role Of Bone Marrow-derived Macrophages Duringmentioning
confidence: 99%
“…The cytokine TWEAK (TNF-like weak inducer of apoptosis) is a member of the TNF superfamily that is expressed in a wide variety of organs [1][2][3] and has been detected at the mRNA or protein level in monocytes/macrophages [4][5][6], kidney tubular cells, endothelial cells, astrocytes, microglia, and certain tumor cell lines [1][2][3]. Its cognate receptor, Fn14, is generally expressed at very low levels in normal tissue, but is highly upregulated in a wide range of organs in contexts of injury and disease [2,3] As mRNA or as protein, Fn14 can be expressed by monocytes/macrophages [6], endothelial cells [7], mesangial cells [8,9], and podocytes [9].…”
Section: Introductionmentioning
confidence: 99%